My Gay Middle Ages - Strouse, A. W. (Book collections on Project MUSE., 2020)
In the world of My Gay Middle Ages, Chaucer and Boethius are the secret-sharers of A.W. Strouse's "gay lifestyle." Where many scholars of the Middle Ages would "get in from behind" on cultural history, Strouse instead does a "reach around." He eschews academic "queer theory" as yet another tedious, normative framework, and writes in the long, fruity tradition of irresponsible, homo-medievalism (a lineage that includes luminaries like Oscar Wilde, who was sustained by his amateur readings of Dante and Abelard during the darks days of his incarceration for crimes of "gross indecency"). Strouse experiences medieval literature and philosophy as a part of his everyday life, and in these prose poems he makes the case for regarding the Middle Ages as a kind of technology of self-preservation, a posture through which to spiritualize the petty indignities of modern urban life. With a Warholian flair for insouciant name-dropping and a Steinian appetite for syntactic perversion, Strouse monumentalizes the medieval within the contemporary and the contemporary within the medieval."Today, almost nobody reads Boethius, which if you ask me is a crying shame. Because Boethius is so gay. First of all, the heroine of the Consolation is this great big fierce diva, whose name is Lady Philosophy. She's a Lady, and she doesn't stand for anybody's crap. At the beginning of the book, Boethius is crying, all alone in prison, depressed that he's lonely and loveless and is going to be killed. Lady Philosophy descends from the heavens, à la Glinda the Good Witch in The Wizard of Oz. The first thing Boethius notices about her is that she's wearing an amazing dress with Greek letters embroidered on it--they stand for practical and theoretical philosophy. Her dress has been torn to shreds by the hands of uncouth philosophers. They didn't know how to treat a lady." (from "My Boethius").